PRODUCTION AND PHYSICOCHEMICAL ANALYSIS OF TOILET SOAP FROM BLENDED OILS - Uduma, Uduma A.; Orverem, Simeon Terkuma; Uduma, Maria B. (FUDMA Journal of Sciences, 2025)
The process of making soap from fatty acids derived from fats and oils is a proven technology. However, the fatty acid makeup of various oils varies, which accounts for the various qualities of the soaps that are created from them. Four different kinds of oils were used in this study. Four distinct toilet soap samples were created by blending them in different proportions. The various characteristics of these samples were examined in order to determine the most cost-effective and suitable soap quality for toilet soap. Every sample’s lathering and cleaning qualities were compared. With 48.40% TFM, 97.40% yield and 8-10 pH, the optimal toilet soap formulation was determined to be a 3:1:3:3 blend of palm kernel oil, palm stearin, beef tallow, and cotton seed oil. All of the blends were examined for a variety of characteristics using accepted techniques, and the results were contrasted with those reported in the literature. The corresponding oils’ iodine and saponification levels were assessed. As a result, soap made with the four blended oils—palm kernel oil, palm stearin, cow tallow fat, and cotton seed oils—in a 3:1:3:3 ratio offers superior qualities than soap made with other blends. Toilet soap has distinct characteristics in terms of its composition, properties and uses, and it’s formulted to serve a specific purpose.